2019
DOI: 10.1186/s12887-019-1875-y
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the prevalence and nature of drug related problems among hospitalised children in the United Kingdom: a systematic review

Abstract: BackgroundProblems arising from medicines usage are recognised as a key patient safety issue. Children are a particular concern, given that they are more likely than adults to experience medication-related harm. While previous reviews have provided an estimate of prevalence in this population, these predate recent developments in the delivery of paediatric care. Hence, there is a need for an updated, focussed and critical review of the prevalence and nature of drug-related problems in hospitalised children in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 86 publications
1
40
0
8
Order By: Relevance
“…Our study found a great proportion of admissions with DRPs, a 45.1% of the cases. Most of the evidence available at a hospital level have focused on specific medical fields [51][52][53] , being limited to ambulatory patients in numerous occasions [54][55][56] . There are, however, some studies focusing on medical specialties, which found a DRP prevalence ranging from 15 to 81% 26,27,[60][61][62] .…”
Section: Discussionmentioning
confidence: 99%
“…Our study found a great proportion of admissions with DRPs, a 45.1% of the cases. Most of the evidence available at a hospital level have focused on specific medical fields [51][52][53] , being limited to ambulatory patients in numerous occasions [54][55][56] . There are, however, some studies focusing on medical specialties, which found a DRP prevalence ranging from 15 to 81% 26,27,[60][61][62] .…”
Section: Discussionmentioning
confidence: 99%
“…Application of pharmacometrics methods in clinical practice give the ability to analyze pharmacokinetics profile and define the optimal doses of drugs in special populations such as children, in whom drugs are not usually studied during clinical trials (Sutherland et al, 2019). It is also possible to quantify doseresponse relationships in these populations (Lala, 2012).…”
Section: Modeling In Drug Therapymentioning
confidence: 99%
“…Während Verordnungsprobleme nur gut 10 % der Meldungen in der vorliegenden Analyse ausmachten, publizierten Hart et al, dass eine medizinisch inkorrekte Verordnung in ihrer Untersuchung mehr als ein Drittel der Berichte ausmachten [15]. Auch andere Studien zeigen, dass die Inzidenz von Verordnungsfehlern direkt hinter Anwendungsfehlern rangiert [13,21,27].…”
Section: Faktoren Die Das Auftreten Von Atbp Beeinflussenunclassified